Quantification of fibrosis by collagen proportionate area predicts hepatic decompensation in hepatitis C cirrhosis. Issue 5 (11th January 2015) - Calvaruso, V.; Di Marco, V.; Bavetta, M. G.; Cabibi, D.; Conte, E.; Bronte, F.; Simone, F.; Burroughs, A. K.; Craxì, A.
Summary Background It is unclear whether the course of cirrhosis and its prognosis are related to the amount of collagen in the liver. Aim To determine whether fibrosis, assessed by collagen proportionate area (CPA) in patients with compensated cirrhosis, is associated with the presence of oesophageal varices, and predict disease decompensation during the follow‐up period. Methods We prospectively evaluated 118 consecutive patients with compensated cirrhosis to correlate fibrosis, assessed by CPA in liver biopsies, with the presence of oesophageal varices (OV) and with the rate of liver decompensation (LD) development during a median follow‐up of 72 months. Results At baseline 38 (32.2%) patients had OV and during the follow‐up (median 72 months, IQR 47–91), 17 patients (14.4%) developed LD. The mean CPA value was different in patients with and without OV (14.8 ± 5.9% vs. 21.6 ± 9.5%, P < 0.001). The best CPA cut‐off for OV by area under the receiver operating characteristic (AUROC) was ≥14% and with multivariate logistic analysis CPA was the only variable associated with OV (OR: 28.32, 95% CI: 6.30–127.28; P < 0.001). By AUROC analysis the best CPA cut‐off to predict LD was 18.0%. By Cox regression multivariate analysis CPA ≥18% (HR: 3.99, 95% CI: 1.04–11.45; P = 0.036), albumin (HR: 0.12, 95% CI: 0.04–0.43; P = 0.001) and presence of OV (HR: 8.15, 95% CI: 2.31–28.78; P = 0.001) were independently associated with LD. Conclusion Quantification of fibrosis by collagen proportionate area allows identification of patients with compensated HCV cirrhosis with a higher likelihood of clinically relevant portal hypertension and a higher risk of decompensation.